Immunotoxic and Genotoxic Potential of Arsenic and its Chemical Species in Goats - Patra, Pabitra Hriday (Medknow Publications & Media Pvt Ltd, 2013)
The study investigated the immunotoxic and genotoxic effect of arsenic and its different species on goats. It was found that arsenic causes haematological crisis. Histopathological changes in spleen and reduced serum immunoglobulin G level without any changes in formazan production in arsenic-treated animals indicated that arsenic is toxic to the humoral immune system. Increased caspase-3 production and higher number of TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick-end labelling)-positive bone marrow cells along with oligonucleosomal DNA fragmentation on agarose gel suggested apoptosis induction by arsenic in the bone marrow cells of goat. Total arsenic concentration in the plasma, bone marrow, and spleen of the exposed group was, respectively, 1.22 ± 0.11, 2.20 ± 0.21, and 3.39 ± 0.14 ppm. Speciation study revealed that arsenite and organoarsenic were the major arsenic species in these samples, suggesting their role in immunotoxic and genotoxic potential in goats.